Pengaruh Persepsi Manfaat Dan Persepsi Kemudahan Terhadap Fintech Menggunakan Tam (Technology Acceptance Model) Di Kota Batam - Khadijah Khadijah; Viola Syukrina E Janrosl (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The application of financial technology will create a disruptive environment in line with the rapid development of technology and digitization. For the financial industry, there is a demand to continue to adapt and make adjustments in its business processes, as the dynamics of the industry change rapidly. Fintech can help MSMEs to get ease and efficiency in the financial area. but not all MSMEs can use fintech for reasons that are difficult to understand and cannot be used when they want to transact financially in business. so that from the problems that occur in the community makes researchers want to research using the TAM model of fintech that has developed in the community. TAM model can be measured by two existing perceptions, namely the perception of ease and perception of the benefits of fintech. The population in this study is people in Batam City. Sampling method is done by purposive sampling that is sampling is done based on certain criteria in accordance with the needs of researchers and using the formula slovin determine the number or size of the sample will be determined. Hypothetical testing in this study was conducted with multiple linear regression tests, simultaneous tests (F tests), determination tests (R2 tests) and t-tests using SPSS 26 applications.